Utilization of Social Media as A Business Tool Among Students in The Perspective of Islamic Business Ethics - Dianah, Azimah; Fitri, Cut Dian; Hawari, Zakia (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The utilization of social media refers to the use of digital platforms that enable interaction and sharing of content in the form of text, images, and videos, for various purposes such as communication, marketing, education, and more, including online businesses. Therefore, it is crucial for students who are frequently engaged with social media to maximize its potential for something more productive, such as running a business in accordance with Islamic business ethics. This research aims to explore the role, challenges, and constraints of social media as a business tool among students of the Faculty of Economics and Islamic Business at UIN Ar-Raniry, Banda Aceh, from the perspective of Islamic business ethics. The study employs a qualitative method with a descriptive approach, conducting in-depth interviews with students actively involved in online business. The informants interviewed for this research include 1 member of PINBIS, 2 academic experts, and 7 students. The results indicate that the utilization of social media as a business tool among students at FEBI UIN Ar-Raniry, Banda Aceh, is well underway but not yet optimal. Not all students can leverage social media as a business tool in line with the perspective of Islamic business ethics, resulting in only a few students starting their online businesses.